Minerals, Toxic Heavy Metals, and Antioxidant Properties of Honeys from Bangladesh - Paul, Sudip; Hossen, Md. Sakib; Tanvir, E. M.; Afroz, Rizwana; Hossen, Delwar; Das, Sagarika; Bhoumik, Nikhil Chandra; Karim, Nurul; Matin, Farha Juliana; Siew , Hua Gan; Khalil, Md. Ibrahim (Hindawi Publishing Corporation, 2017)
The study reports on major and trace elements as well as antioxidant properties of honey samples from Bangladesh. Four major cationic elements, seven trace elements, and three heavy metals were determined in the 12 honey samples using atomic absorption spectrophotometer. Nutritional values in these honey samples were further investigated according to their antioxidant properties. The content of major elements was in the range of 62.75–616.58, 579.48–2219.43, 69.42–632.25, and 0.13–1.20mg/kg for sodium, potassium, magnesium, and calcium, respectively. The trace elements varied in the range of 0.41–28, 0.12–3.54, 1.54–2.85, 0.29– 0.59, 0.02–0.35, and 0.01–0.06mg/kg for iron, zinc, copper, nickel, cobalt, and cadmium, respectively. Among the heavy metals, only lead (0.17–2.19 mg/kg) was detected.The results of antioxidant analysis based on phenolics, flavonoids, ascorbic acid, reducing sugar, and proteins (as nonphenolic antioxidants) revealed that multifloral raw honey samples contain significantly higher levels of reducing agents than monofloral and commercial brand honeys. The study provides a useful insight on the minerals, heavy metals, and antioxidant properties of honey samples commonly consumed in Bangladesh and found to be rich source of antioxidants and minerals. Some samples might pose some risk to the health due to lead contamination.